Application of the rating scale model to examine the psychometric properties of the self-control scale - Garrido, Sebastian Jesús (2017)
Considering the theoretical, empirical, and practical importance of self-control assessment through valid and reliable instruments, the present study examined the psychometric properties of the original version of the Self-Control Scale (SCS). To this end, the rating scale model was used to estimate unidimensionality, the adequacy of response categories, and participant fit. These analyses were conducted using a convenience sample of 1072 Argentine university students. Among other findings, it was observed that the SCS makes it possible to assess the self-control construct unidimensionally and that a version of the scale with 3 response categories would be more adequate for measuring self-control than the original 5-category version. However, it was found that the new configuration of response categories led to differential functioning in 3 items depending on the participants' sex. Finally, the person-item distribution map showed a lack of elements at the top and bottom of the self-control continuum.